Selection of Methods to Provide End-to-End Email Traffic Security - Petrosyan, Arthur S.; Petrosyan, Gurgen S. (Mathematical Problems of Computer Science, 2021)
he goal of the research described in this paper is to select methods of securing Email traffic. While it is known that Email service is not secure by default, both end users and service providers can implement available securing mechanisms to ensure end-to-end Email traffic security as much as possible. Latest developments and research in this area, like SMTP MTA Strict Transport Security (STS) and SMTP TLS Reporting are presented. This paper includes a best practice configuration of protection methods for both Mail User Agent (MUA) and Mail Transfer Agent (MTA). Recommendations given are oriented for the Members of Academic Scientific Research Computer Network of Armenia (ASNET-AM) in regard to secure use of ASNET-AM Email Service.